Advanced Bifunctional Electrochemical Catalysts for Metal-Air Batteries - Wang, Yan-Jie; Yuan, Rusheng; Ignaszak, Anna; Wilkinson, David P.; Zhang, Jiujun; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Metal-air batteries (MABs) have attracted attention because of their high specific energy, low cost, and safety features. This book discusses science and technology including material selection, synthesis, characterization, and their applications in MABs. It comprehensively describes various composite bifunctional electrocatalysts, corrosion/oxidation of carbon-containing air cathode catalysts, and how improvements can be achieved in the catalytic activities of oxygen reduction reaction and oxygen evolution reaction and their durability/stability. This book also analyzes, compares, and discusses composite bifunctional electrocatalysts in the applications of MABs, matching the fast information of commercial MABs in requirements. Aimed at researchers and industry professionals, this comprehensive work provides readers with an appreciation for what bifunctional composite electrocatalysts are capable of, how this field has grown in the past decades, and how bifunctional composite electrocatalysts can significantly improve the performance of MABs. It also offers suggestions for future research directions to overcome technical challenges and further facilitate research and development in this important area.
Chapter 1 Description of bifunctional electrocatalysts for metal-air batteries -- 1.1 Types and Characteristics of Metal-Air Batteries -- 1.2 Current State of Bifunctional Catalysts in Metal-Air Batteries -- 1.3 Exploration and Development of Advanced Bifunctional Catalysts -- 1.4 Chapter Summary -- References -- 2 Fundamentals of Bifunctional Composite Electrocatalysts -- 2.1 Working Mechanisms of Bifunctional Catalysts in Metal-Air Batteries -- 2.1.1. Mechanisms in Aqueous Electrolytes -- 2.1.2. Mechanisms in Nonaqueous Electrolytes -- 2.1.3. Mechanisms in Hybrid Electrolytes -- 2.1.4. Mechanisms in Solid-State Electrolytes -- 2.2 Design Principles of Bifunctional Composite Catalysts -- 2.3 Synergistic Effect and Its Characterization for Major Components -- 2.4 Chapter Summary -- References -- 3 Carbon-based bifunctional composite electrocatalysts -- 3.1 Composites of Different Carbons -- 3.1.1 Single Carbon Materials -- 3.1.2 Composites of Different Carbons -- 3.2 Composites of Carbon and Nonmetal -- 3.2.1 Composites of Carbon and Single Element -- 3.2.1.1 N-Doped Carbons -- 3.2.1.2 Other Heteroatom-Doped Carbons -- 3.2.2 Composites of Carbon and Dual Elements -- 3.3 Composites of Carbon and Metal -- 3.3.1 Composites of Carbon and Noble Metal or Noble Metal-Alloy -- 3.3.1.1 Composites of Carbon and Pt or Pt-alloy -- 3.3.1.2 Composites of Carbon and Other Noble Metal or Alloy -- 3.3.2 Composites of Carbon and Nonnoble Metal -- 3.4 Composites of Carbon and Oxide -- 3.4.1 Composites of Carbon and Perovskite Oxide -- 3.4.2 Composites of Carbon and Spinel Oxide -- 3.4.3 Composites of Carbon and Other Oxide -- 3.5 Composites of Carbon and Nitride -- 3.6 Composites of Carbon and Carbide -- 3.7 Other Carbon-Based Composites -- 3.7.1 Other Carbon-Based Binary Composites -- 3.7.2 Other Carbon-Based Ternary Composites -- 3.8 Chapter Summary -- References -- 4 Doped Carbon-Based Bifunctional Composite Electrocatalysts -- 4.1 Composites of Doped Carbon and Carbon -- 4.2 Composites of Doped Carbon and Oxide -- 4.2.1 Composites of Single Element-Doped Carbon and Oxide -- 4.2.1.1 Composites of Single Element-Doped Carbon and -- Perovskite Oxide -- 4.2.1.2 Composites of Single Element-Doped Carbon and Spinel -- Oxide -- 4.2.1.3 Composites of Single Element-Doped Carbon and Other -- Oxide -- 4.2.2 Composites of Dual Elements Co-Doped Carbon and Oxide -- 4.3 Composites of Doped Carbon and Metal(s) -- 4.3.1. Composites of Single Element-Doped Carbon and Metal(s) -- 4.3.2. Composites of Dual Elements Co-Doped Carbon and Metal(s) -- 4.4 Composites of Doped Carbon and Nitride -- 4.5 Other Doped Carbon-Based Composites -- 4.6 Chapter Summary -- References -- 5 Noncarbon-Based Bifunctional Composite Electrocatalysts -- 5.1 Composites of Different Metals -- 5.2 Composites of Oxide and Metal -- 5.2.1 Metal Oxides -- 5.2.2 Composites of Perovskite Oxide and Metal -- 5.2.3 Composites of Spinel Oxide and Metal -- 5.2.4 Composites of Other Oxide and Metal -- 5.3 Other Noncarbon-Based Composites -- 5.4 Chapter Summary -- References -- 6 Catalyst Applications in Metal-Air Batteries -- 6.1 Requirements for Electrocatalysts in Metal-Air Batteries -- 6.2 Comparison of Battery Performance and Bifunctionality -- 6.3 Optimization of Electrocatalysts in Metal-Air Batteries -- 6.4 Chapter Summary -- 6.4.1 Conclusions -- 6.4.2 Challenges -- 6.4.3 Future Research Directions -- References.
Includes bibliographical references and index.
Also available in print format.
Keywords: Catalysts; Electrocatalysis; Electric batteries -- Materials; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; TECHNOLOGY & ENGINEERING / Material Science; Electronic books